High resolution luminescence spectroscopy and thermoluminescence of different size LaPO4:Eu3+ nanoparticles - Gavrilović, Tamara; Laganovska, Katrīna; Zolotarjovs, Aleksejs; Smits, Krisjanis; Jovanović, Dragana J.; Dramićanin, Miroslav D. (Elsevier B.V., 2018)
Nanoparticles (5 nm) and nanorods (2 nm × 15 nm and 4 nm × 20 nm) of monoclinic monazite LaPO4:Eu3+ were prepared by reverse micelle and co-precipitation techniques. Effects of the particle size and surface defects on the intensity of luminescence and the emission spectrum shapes were analyzed by high resolution spectroscopy under laser (266 nm) and X-rays excitation. All synthesized LaPO4:Eu3+ samples showed similar spectral features with characteristic Eu3+ ions emission bands: 5D0→7F0 centered at 578.4 nm, magnetic-dipole transition 5D0→7F1 at 588–595 nm, electric-dipole transition 5D0→7F2 at 611.5–620.5 nm, 5D0→7F3 at (648–652 nm) and 5D0→7F4 at (684–702.5 nm), with the most dominant electric-dipole 5D0→7F2 transition. Additionally, the thermally stimulated luminescence was studied for the most dominant peak at 611.5 nm. It was shown that the Eu3+ doping creates traps in all samples. Two prominent and well resolved glow peaks at 58.7 K and 172.3 K were detected for 5 nm nanoparticles, while low-intensity glow-peaks at 212.1 K and 212.2 K were observed in the X-rays irradiated nanorods. Displayed glows could be attributed to free and bound electrons and holes or to the recombination of electrons of ionized oxygen vacancies with photogenerated holes. To obtain information about the processes and specific defect type it is necessary to carry out additional analysis for all synthesized samples. The glow curves were analyzed and trap parameters were estimated and discussed throughout the paper.
T. G. acknowledges the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/215 (1.1.1.2/16/I/001). K. S. and K. L. acknowledge the Latvian National Research Program IMIS2. The authors from Vinča Institute of Nuclear Sciences acknowledge the financial support of the Ministry of Education, Science and Technological Development of the Republic of Serbia (Project No: 45020 and 172056 ).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; High resolution spectroscopy; LaPO4:Eu3+; Thermo-stimulated luminescence; X-ray excitation